2020
DOI: 10.1016/j.nbd.2020.105085
|View full text |Cite
|
Sign up to set email alerts
|

Divergent FUS phosphorylation in primate and mouse cells following double-strand DNA damage

Abstract: Fused in sarcoma (FUS) is a RNA/DNA protein involved in multiple nuclear and cytoplasmic functions including transcription, splicing, mRNA trafficking, and stress granule formation. To accomplish these many functions, FUS must shuttle between cellular compartments in a highly regulated manner. When shuttling is disrupted, FUS abnormally accumulates into cytoplasmic inclusions that can be toxic. Disrupted shuttling of FUS into the nucleus is a hallmark of ~10% of frontotemporal lobar degeneration (FTLD) cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…We genetically fused APEX2 to the N-terminus of three FUS protein variants via a (GGGS) 3 linker to generate three Twin-Strep-tagged® constructs: 1) wild-type human FUS (FUS WT), 2) phosphomimetic FUS (FUS PM), and 3) the ALS-linked P525L mutant FUS (FUS P525L) (Figure 1A). FUS PM was generated by substituting the 12 consensus S/T_Q residues, which are phosphorylated by DNA-PK following DSB, with the negatively charged amino acid aspartate (Deng et al ., 2014b; Johnson et al ., 2020). The FUS P525L mutation was first identified in 2012 and causes a severe form of juvenile ALS (Conte et al , 2012; Zhou et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We genetically fused APEX2 to the N-terminus of three FUS protein variants via a (GGGS) 3 linker to generate three Twin-Strep-tagged® constructs: 1) wild-type human FUS (FUS WT), 2) phosphomimetic FUS (FUS PM), and 3) the ALS-linked P525L mutant FUS (FUS P525L) (Figure 1A). FUS PM was generated by substituting the 12 consensus S/T_Q residues, which are phosphorylated by DNA-PK following DSB, with the negatively charged amino acid aspartate (Deng et al ., 2014b; Johnson et al ., 2020). The FUS P525L mutation was first identified in 2012 and causes a severe form of juvenile ALS (Conte et al , 2012; Zhou et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…We wanted to ensure that FUS PM bound proteins in a similar manner to biological relevant N-terminally phosphorylated FUS. Thus, we also confirmed that endogenous UPF1 binds preferentially to FUS treated with calicheamicin γ1 (CLM), a known inducer of N-terminal FUS phosphorylation (Deng et al ., 2014b; Johnson et al ., 2020; Rhoads et al ., 2018) (Supplementary Figure 4). Lastly, we confirmed the interaction of three novel binding partners, VPS35, MOV10 and CLTA, to our three FUS variants (Figure 4A, red bar).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations